Rancang Bangun Sistem Informasi Hitung Tani (SiTung Tani) Menggunakan Metode Ubinan Berbasis Android - Effendi, Diana; Dhaniawaty, Rani Puspita; Hardiyana, Bella (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2022)
In the current era of digitalization, technology can facilitate all kinds of activities, starting from education, business, health, and agriculture. The use of technology in agriculture can help the managerial processes which are often a problem for farmers. Hitung Tani Application System (SiTung Tani) is an Android-based application, which can assist farmers in preparing budget plans regarding all cost requirements before the farming activity takes place. The method used in building SiTung Tani is the Ubinan method which is used to calculate estimates of various costs and the system approach method used is the object-oriented method. The Sabilulungan Farmer Group is located in a rural area, so there are still many farmers who do not understand and use technology in all farming activities. In addition, the obstacles faced by farmers in this farmer group are that they rarely calculate mathematically how many plant seeds are needed according to the land they have and rarely calculate the estimated cost of production and yields which result in losses. From the problems that exist in the farmer groups, a farmer count application system is needed that can assist farmers in compiling a budget plan for cost requirements during the process of farming activities to increase farm productivity, can calculate the estimated income and profits that will be obtained by farmers and can provide recommendations